Evaluasi Dan Penyesuaian Sistem Ventilasi Pada Tambang Batubara Bawah Tanah Lubang SD-C2 Manual PT. Nusa Alam Lestari Kecamatan Talawi kota Sawahlunto Provinsi Sumatera Barat - khazana tulistra; mulya gusman (Departemen Teknik Pertambangan FT UNP, 2022)
The ventilation system in Hole SD-C2 PT. Nusa Alam Lestari is a forcing system and does not apply an exhaust fan. So that dirty air from the mining front is not immediately transported out, and the clean air that flows from the main blower is mixed with dirty air coming from the mining front. Some leaks are still detected in the ventilation line. Leaks are still detected in the ventilation path at a depth of 2 m, 30 m, 50 m, 60 m, and 70 m from the opening. After taking measurements at several points, the temperature value in the SD-C2 Manual Hole is 27-290C. Conditions that exceed Kepmen 1827 K/30/MEM/2018. The research method used is the Applied Method (Sugiono, 2013:2). The data sources used are primary data and secondary data, with problem-solving using quantitative and qualitative data. Solving the problem by calculating the air requirement for workers, tools, and dilution of methane gas to get the total air requirement. The total amount of air required at the underground mine of PT. Nusa Alam Lestari at the location of the SD-C2 Manual opening for 15 workers (0.45 m 3 /s), the air required in the work front is (6.6248 m 3 /s) and to dilute methane gas (0.099 m 3 /s ) with the overall air quantity (10.411 m 3 /s). Based on the calculation of the required air quantity, the hole requires 4 blowers to meet these needs, and to make the condition of the hole more comfortable, it is necessary to add a suction fan unit to speed up the transportation of polluted air out of the hole. Ventilation system modeling produces a 3D model of the ventilation system before and after the addition of the blower.